A midsummer night's dream [videorecording (DVD)] - Brown, Joe E. (Joe Evan), 1892-1973; Powell, Dick, 1904-1963; Rooney, Mickey; De Havilland, Olivia; Shakespeare, William, 1564-1616 (Distributed by Warner Home Video, 2007)
Love is blind, fickle and true. Theseus, Duke of Athens, is going to marry Hyppolyta, Queen of the Amazons. Demetrius is engaged to Hermia, but Hermia loves Lysander. Helena loves Demetrius. Oberon and Titania, of the kingdom of fairies, have a slight quarrel about whether or not the boy Titania is raising will join Titania's band or Oberon's, so Oberon tries to get the boy from her by using some magic. Lysander and Hermina meet in the forest. Helena and Demetrius are there as well. There are actors practicing a play for the upcoming wedding of Theseus and Hippolyta. Due to some misunderstandings by Puck, the whole thing becomes a little bit more confused.